Предмет: Математика,
автор: guskova79
упростите:
(-0,7х+0,6у)5-3(0,4у-1,5х)=
2/9(1,8-1 1/а)-1 1/6(1,2-2/7а)=
Ответы
Автор ответа:
0
(-0,7х+0,6у)5-3(0,4у-1,5х)=-3,5х+3у-1,2у+4,5у=7,5у-4,7х
2/9·18/10-2/9·3/2а-7/6·12/10+7/6·2/7а=2/5-1/3а-7/5+1/3а=-2/5=-0,4
2/9·18/10-2/9·3/2а-7/6·12/10+7/6·2/7а=2/5-1/3а-7/5+1/3а=-2/5=-0,4
Похожие вопросы
Предмет: Українська мова,
автор: urovavitalina207
Предмет: Математика,
автор: elizabethtarasova919
Предмет: Физика,
автор: tuxtamisbexruzjon
Предмет: Математика,
автор: olgailina1973